Potential of some soil bacteria for degradation of organophosphorus pesticides - a review - SANDHYA GOEL,; NARENDRA KUMAR, (International Journal of Pharma and Bio Sciences, 2017)
Organophosphate pesticides are commonly used in agriculture for pest control. The short and long-term exposures to Organophosphates induce inhibition of acetyl cholinesterase (AchE) activity, thus leading to nervous impairment in humans. This review records various aspects viz., organophosphates in soil, organophosphates toxicity, biodegradation of organophosphorus pesticides, bacterial degradation, enzymatic degradation of organophosphorus pesticides. The literature shows that there has been variation in Bacillus, Arthrobacter, Xanthomonas and Actinomyces population which indicates that OP pesticides had either stimulatory or inhibitory effects on different microbial groups. The bacterial species used for degradation are viz., Pseudomonas putida, Acinetobacter rhizosphaerae Pseudomonas diminuta MG and Flavobacterium ATCC 27551, Nocardiodes simplex Stenotrophomonas malthophilia, Proteus vulgaris, Vibrio metschinkouii, Serratia ficaria, Serratia spp.,Yersinia enterocolitica.Bacillus amyloliquefaciens, Bacillus licheniformis, Pseudomonas species, Staphylococcus species. Inspite of this many catabolic plasmids have been found in species of Pseudomonas, Alcaligenes, Actinobacter, Flavobacterium, Klebsiella, Moraxella and Arthrobacter, which have degradative potential. These kind of ecofriendly bacteria can be used to encourage and motivate the farmers to use natural biological pesticides